β3GnT2 Maintains Adenylyl Cyclase-3 Signaling and Axon Guidance Molecule Expression in the Olfactory Epithelium - Henion, Timothy R. (Society for Neuroscience, 2011)
In the olfactory epithelium (OE), odorant receptor stimulation generates cAMP signals that function in both odor detection and the regulation of axon guidance molecule expression. The enzyme that synthesizes cAMP, adenylyl cyclase 3 (AC3), is coexpressed in olfactory sensory neurons (OSNs) with poly-N-acetyllactosamine (PLN) oligosaccharides determined by the glycosyltransferase β3GnT2. The loss of either enzyme results in similar defects in olfactory bulb (OB) innervation and OSN survival, suggesting that glycosylation may be important for AC3 function. We show here that AC3 is extensively modified with N-linked PLN, which is essential for AC3 activity and localization. On Western blots, AC3 from the wild-type OE migrates diffusely as a heavily glycosylated 200 kDa band that interacts with the PLN-binding lectin LEA. AC3 from the β3GnT2(−/−) OE loses these PLN modifications, migrating instead as a 140 kDa glycoprotein. Furthermore, basal and forskolin-stimulated cAMP production is reduced 80–90% in the β3GnT2(−/−) OE. Although AC3 traffics normally to null OSN cilia, it is absent from axon projections that aberrantly target the OB. The cAMP-dependent guidance receptor neuropilin-1 is also lost from β3GnT2(−/−) OSNs and axons, while semaphorin-3A ligand expression is upregulated. In addition, kirrel2, a mosaically expressed adhesion molecule that functions in axon sorting, is absent from β3GnT2(−/−) OB projections. These results demonstrate that PLN glycans are essential in OSNs for proper AC3 localization and function. We propose that the loss of cAMP-dependent guidance cues is also a critical factor in the severe axon guidance defects observed in β3GnT2(−/−) mice.